2020
DOI: 10.1080/14786419.2020.1749609
|View full text |Cite
|
Sign up to set email alerts
|

Three new diterpenoids from Euphorbia peplus

Abstract: Three new diterpenoids (1-3) (two abietane type diterpenoids and a paralianone type diterpenoid), together with four known compounds (4-7) were isolated from the whole plants of Euphorbia peplus. Their structures were elucidated through spectroscopic analysis and physicochemical characteristics. The cytotoxic activities of compounds 1-7 against five human tumor cell lines were evaluated, however, they were inactive at the concentration of 40 μM. The compound 3 enhanced lysosomal biogenesis with Lyso Tracker st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Most of the studied species contained both polycyclic and macrocyclic diterpenes and included E. lathyris [ 31 ], E. stracheyi [ 32 ], E. royleana [ 33 ], E. antiquorum [ 34 ], E. kansuensis [ 35 , 36 ], E. prolifera [ 37 ], E. peplus [ 38 ], E. aellenii [ 39 ], E. pilosa [ 40 ], E. saudiarabica [ 28 ], E. marginata [ 41 ], E. neriifolia [ 42 ], E. resinifera [ 43 ], E. pekinensis [ 44 ], E. hylonoma [ 45 ], E. milii [ 46 ], E. wallichii [ 47 ], and E. ebracteolata [ 48 ]. While others contained only macrocyclic diterpenes like E. esula [ 49 ], E. helioscopia [ 50 ], E. yinshanica [ 51 ], E. grandicornis [ 52 ], and E. kansui [ 53 ].…”
Section: Occurrence Of Euphorbia Diterpenesmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studied species contained both polycyclic and macrocyclic diterpenes and included E. lathyris [ 31 ], E. stracheyi [ 32 ], E. royleana [ 33 ], E. antiquorum [ 34 ], E. kansuensis [ 35 , 36 ], E. prolifera [ 37 ], E. peplus [ 38 ], E. aellenii [ 39 ], E. pilosa [ 40 ], E. saudiarabica [ 28 ], E. marginata [ 41 ], E. neriifolia [ 42 ], E. resinifera [ 43 ], E. pekinensis [ 44 ], E. hylonoma [ 45 ], E. milii [ 46 ], E. wallichii [ 47 ], and E. ebracteolata [ 48 ]. While others contained only macrocyclic diterpenes like E. esula [ 49 ], E. helioscopia [ 50 ], E. yinshanica [ 51 ], E. grandicornis [ 52 ], and E. kansui [ 53 ].…”
Section: Occurrence Of Euphorbia Diterpenesmentioning
confidence: 99%
“…Of this, E. esula [ 49 ] had the highest number of isolated diterpenes ( n = 44), of which the majority were jatrophane and lathyrane diterpenes, followed by E. royleana [ 33 ] ( n = 36). Others were E. neriifolia [ 42 ], ( n = 32), E. lathyris ( n = 21) [ 31 ] ( n = 28), E. kansui [ 53 ] ( n = 23), E. stracheyi [ 32 ] ( n = 22), E. peplus [ 38 ] ( n = 22), E. antiquorum [ 34 ], ( n = 21) and E. marginata [ 41 ] ( n = 20). While other species reported only one or two diterpenes such as E. gaditana [ 27 ] ( n = 1), E. kopetdaghi [ 25 ] ( n = 2), E. aellenii [ 39 ] ( n = 2), E. pilosa ( n = 2) and E. grandicornis ( n = 2) ( Table 1 ).…”
Section: Occurrence Of Euphorbia Diterpenesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group discovered ingenane type diterpenoids 20-deoxyingenol and its analogues from E. peplus, possessing activity to promote lysosome biogenesis, limit amyloid plaque formation in APP/SP1 mice's brain, which suggested that the potential of these compounds for the treatment of Alzheimer disease [10]. The subsequent phytochemical studies of the plants of the genus Euphorbia led to isolation of several novel diterpenoids with significant bioactivities [11][12][13][14][15][16]. In our continuing efforts to uncover structurally novel diterpenes capable of inducing lysosomal biogenesis, four new jatrophane type diterpenoids euphopepluanones F − K (1 − 4), along with eight known diterpenoids (5 − 12) were obtained from the seed of E. peplus (Fig.…”
Section: Introductionmentioning
confidence: 99%